Assessment of the Quality of Drinking Water for Plants in the Al-Karkh, Baghdad, Iraq - Hasan, Zainab I.; Taleb, Adel H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The study aims to assess some physical, chemical, and bacterial characteristics of two drinking water treatment plants of Al- Dora and Al-Qadisiya in the area of ​​Karkh, Baghdad, Iraq. The areas covered by each plants and these sites of areas selected as the nearest and the farthest point from plants, for winter and summer season. Some physicochemical parameters of water quality were taken in this study and these parameters were temperature water, pH, electrical conductivity, total dissolved solids, free residual chlorine, calcium, magnesium, nitrate, nitrite, sulphate and heavy metals (lead). In addition to four bacterial indicators of drinking water pollution (APC, Total Coliform, Fecal Coliform and Salmonella spp.). The results showed within the permissible limits for Iraqi criteria and standards for drinking water.